Effects of irradiance and penetration resistance on root and shoot growth of rice (Dhaka University Journal of Biological Sciences, 2011)
Plants of BR-29 rice were grown at low (0.05 MPa) and high (0.9 MPa) penetration resistances under low (187 μmol/sec/m2) and high (375 μmol/sec/m2) ) irradiances for three and nine days. There was no significant effect of irradiance (p > 0.05) on seminal root axis lengths of rice at three days after transplanting. At nine days after transplanting, seminal root axis lengths were significantly greater in high than low irradiances (p < 0.05), but only in low penetration resistance. Significant effect (p < 0.05) was also found on number of laterals in both low and high penetration resistances. In case of shoot lengths no significant differences (P > 0.05) were found at three or nine days after transplanting between low and high irradiances. But increase in leaf length with time was higher at low irradiance (up to 120 hours) than at high irradiance (up to 96 hours). However, in the phytotron, plants were getting irradiance at a constant rate for the total day length (12 hours) with little mutual leaf shading. It was assumed that these conditions would be likely to give a rate of photosynthesis close to the maximum. Therefore, it may be concluded from this experiment that irradiance can have more prominent effect on root than shoot at different penetration resistances in soil.Key words: Irradiance; Penetration resistance; Growth; RiceDOI: http://dx.doi.org/10.3329/dujbs.v20i1.8839Dhaka Univ. J. Biol. Sci. 20(1): 65-70, 2011 (January)